A rare case of abdominal pain and hematochezia: case report and literature review - Guo, Wenjuan; Ling, Min; Shi, Yanfen; Zhang, Minggang; Cheng, Xiaoyun; Chen, Jianan; Wang, Xiaodi; Du, Shiyu (Frontiers in Medicine, 2025)
Idiopathic myointimal hyperplasia of the mesenteric veins (IMHMV) is a rare, non-thrombotic, non-inflammatory cause of chronic colonic ischemia, often misdiagnosed as inflammatory bowel disease (IBD) or ischemic colitis due to overlapping clinical features. We present the case of a 65-year-old man with progressive abdominal pain and hematochezia, initially treated as ischemic colitis without improvement. Surgical resection was eventually performed, and definitive diagnosis of IMHMV was established through histopathological evaluation, which revealed characteristic intimal smooth muscle proliferation in mesenteric veins. This report reviews the diagnostic challenges, histologic features, and clinical relevance of IMHMV, emphasizing the importance of early recognition and consideration of this entity in refractory colonic ischemia. Routine use of vascular imaging may help distinguish IMHMV from occult mesenteric arteriovenous malformations.